Telaah Kritis Pemikiran Muhammad Syuhudi Ismail: Perspektif Pemahaman Tekstual dan Kontekstual Hadis - Abdurahim, Mika; Sa’adah, Dadah (AHKAM, 2025)
Muhammad Syuhudi Ismail is known as one of the scholars w ho is usually called Syuhudi Ismail, who has made important contributions to the development of hadith studies, especially in the context of understanding the meaning of hadith according to the situation and conditions of contemporary society. Therefore, he provides his own color in understanding hadith, especially from a contextual perspective, although he does not forget the textual perspective. This research aims to analyze Syuhudi Ismail's views regarding methods of understanding hadith through textual and contextual approaches. This research uses a qualitative method with a descriptive-analytical approach, which examines the works of Syuhudi Ismail and his thoughts regarding hadith study methodology. In this analysis, it is explained how Syuhudi Ismail emphasizes the importance of maintaining a balance between a textual approach, which focuses on the literal meaning of the hadith, and a contextual approach, which takes into account the social, cultural and historical background. The research results show that Syuhudi Ismail's views on hadith make a significant contribution to the development of contemporary hadith studies, especially in efforts to understand hadith from various angles in order to face the challenges of modernity and the relevance of hadith in everyday life. The conclusion of this research is that Syuhudi Ismail's view emphasizes the importance of understanding hadith not only from the literal side of the text, but also from the social, cultural and historical context in which the hadith was uttered. With this contextual understanding, the messages and teachings contained in the hadith can be more relevant to apply today.